Guidelines for supporting children with disabilities' play. Methodologies, tools, and contexts - Bianquin, Nicole (De Gruyter, 2018)
Play for the sake of play, without any secondary goals, if of utmost importance for children's wellbeing and development. In this book you'll find guidelines to support children with disabilities' play. Providing ready-to-use information in a lay-person language, this book is for parents, teachers, rehabilitation professionals, toy manufacturers, policy makers and all persons interested in the topic of play for children with disabilities.